Pengaruh Pengendalian Internal, Moralitas Individu, Kepuasan Kerja, Dan Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi - Ni Luh Kadek Sri Damayanti; Cok Gede Bayu Putra (UNHI Press, 2023)
This study was made to examine the effect of internal control, individual morality, job satisfaction, and compensation suitability in an effort to reduce the tendency of accounting fraud in the Singapadu Village Cooperative. All employees of the Singapadu Village-wide Multipurpose Cooperative were used as the research population. The sample used amounted to 45 people which were further investigated by multiple linear regression analysis techniques. This study shows that the tendency of fraud will increase when the internal control in the organization is bad. Low individual morality causes the possibility of employees to commit fraud is higher. Low job satisfaction will encourage employees to commit fraud because they want to get satisfaction at work. The tendency of fraud will also be higher when the compensation provided by the company does not match the expectations and workload of the employees.